Expanding vocabulary through translation - Koletnik, Melita (Scripta manent (Ljubljana), 2012)
Owing mostly to the overwhelming tide of a communicative approach in foreign language teaching, translation was widely excluded from language classes for much of the 20th century. Nevertheless, translation never went away completely; it patiently waited for a time when the language teaching community would again discover synergies between translation and established approaches, thence reassess its lost potential. As is established herein, such potential is at its greatest and most effective in relation to vocabulary, where - based on an eclectic method which can be applied at all stages in specialised and general language teaching the author believes translation is both necessary and effective. This paper, building on the theoretical and methodological frameworks, together with the authors own classroom observations, reassesses the role of translation and proposes a set of activities which could be used by teachers of English for specific purposes and translator trainers alike. It concludes with a recommendation as to the universal applicability of translation, especially in the context of languages for specific purposes and translator training.
Keywords: Besedišče; communicative approach; grammar-translation method; komunikacijski pristop; leksikalen pristop; lexical approach; ne zaključna dela; prevajanje; Prevajanje in tolmačenje; translation; vocabulary